Fantastic theater puppets and plays for young performers and young audiences - Sierra, Judy (H.W. Wilson, 1991)
Thirty puppet plays adapted from nursery rhymes, folk songs, fables, poetry, folktales, and myths with instructional chapters on making and using rod and shadow puppets and puppet stages.